Heterogeneous effects of agricultural insurance on agricultural green development: evidence from Sub national economies of India - Mohd Yousuf Malik; Ashu Tiwari; Waheedullah Hemat (Discover Sustainability)
Abstract The current paper aims to assess the relative competitiveness of agricultural green development across 27 Indian states and explore the factors influencing this development. Given India's significant role as a global producer of various crops such as rice, wheat, sugarcane, cotton, and pulses, and with approximately 43.96 percent of the labour force engaged in agriculture, the sector's performance is crucial for achieving Sustainable Development Goals (SDGs). The green development index has been created through the entropy method by using seven variables, where Uttar Pradesh and Telangana demonstrate higher green competitiveness. Conversely, states like Himachal Pradesh, Uttarakhand, and Punjab exhibit lower levels of green competitiveness due to their elevated consumption of fertilizers and pesticides. To understand the determinants of agricultural green development competitiveness, Quantile regression has been employed. The findings highlight a positive relationship between (the endogenous variable) and Per capita income, Bank branches in rural areas, hectares of land insured and capital expenditure on agriculture whereas increased cropping intensity and power availability per capita has negative relationships. Furthermore, employing the Dumitrescu and Hurlin (2012) panel Granger causality test reveals that economic growth at the state level in India precedes and influences agricultural green development. This suggests a dynamic relationship wherein economic progress fosters advancements in agricultural sustainability.